Scutellarin Improves Type 2 Diabetic Cardiomyopathy by Regulating Cardiomyocyte Autophagy and Apoptosis. (6th May 2022) - Su, Yanmei; Fan, Xiaoming; Li, Siman; Li, Zhigang; Tian, Ming; Li, Shude
Abstract : Diabetes cardiomyopathy has metabolic disorder and abnormality of cardiomyocytes, which is closely related to autophagy or apoptosis of cardiomyocytes. Scutellarin (SCU) is an important monomer extracted from Erigeron breviscapus (vant.) Hand.-Mazz. This study was conducted to investigate the function of SCU on apoptosis and autophagy of myocardial cells. We established a model of type 2 diabetic cardiomyopathy by high-fat and high-sugar diet. The results indicated that SCU downregulated blood glucose, total cholesterol (TC), triglyceride (TG), and low-density lipoprotein (LDL) levels and upregulated high-density lipoprotein (HDL) level. In addition, SCU downregulated lactic dehydrogenase 1 (LDH1) and creatine kinase (CK) levels. Meanwhile, SCU improved the myocardium morphology and reduced myocardial apoptosis. Furthermore, SCU promoted the mRNA and protein expression of autophagy-related factors (Beclin-1 and LC3-II) and inhibited the mRNA and protein expression of apoptosis-related factors (caspase-3, caspase-8, caspase-9, caspase-12, Bax, and Cyt-C). In conclusion, SCU can promote autophagy signal pathway by upregulating the autophagy-related factors and inhibit the apoptotic signal pathway by downregulating apoptosis-related factors, thereby relieving type 2 diabetic cardiomyopathy (T2DC).